2017
DOI: 10.15740/has/ijpp/10.1/96-102
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of newly developed variable rate sprayer for spray deposition in guava orchard

Abstract: Application of pesticide inside orchards with conventional sprayers often results in an inefficient application as these are constant rate applicators and also the significant amount of pesticide gets lost in spaces between trees. To reduce the pesticide losses inside orchards, a variable rate sprayer was developed which sprayed only after the occurrence of the tree and according to the size of the tree. The performance of the developed variable rate sprayer was evaluated inside guava trees to quantify the spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several studies have analyzed the effect of forward speed on spray deposition and drift [ 93 , 133 ]. Salyani [ 134 ] reported an inverse relationship between deposition and travel speed, and deposit uniformity and travel speed.…”
Section: Other Factors Affecting Performance In Sprayingmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have analyzed the effect of forward speed on spray deposition and drift [ 93 , 133 ]. Salyani [ 134 ] reported an inverse relationship between deposition and travel speed, and deposit uniformity and travel speed.…”
Section: Other Factors Affecting Performance In Sprayingmentioning
confidence: 99%
“…Salyani [ 134 ] reported an inverse relationship between deposition and travel speed, and deposit uniformity and travel speed. Others reported a non-significant effect of travel speed on spray deposition for variable-rate sprayers using ultrasonic sensors for canopy detection [ 93 , 111 , 135 ], although the uniformity of deposition decreased as the speed increased due to bent and distortion of air-jet [ 133 ]. Whitney et al [ 136 ] reported an enhanced deposition on the upper leaf surface with increasing forward speed of air blast sprayers in citrus, but no significant increase in the deposition was reported on the lower leaf surface.…”
Section: Other Factors Affecting Performance In Sprayingmentioning
confidence: 99%
See 3 more Smart Citations